As mudanças na política externa contemporânea da Turquia: as respostas diante das revoltas árabes pós-2011 - Roberto, Willian Moraes (2018)
Turkey, located at a strategic point between Europe and the Middle East, has historically been a relevant actor on the international scene. Since 2003, with the AKP (Justice and Development Party) coming to power, the country has stood out even more. On the one hand, its political model gained prominence due to the fact that an Islamic-rooted party began to cohabit secular bureaucratic institutions, accepting democratic rules and achieving high rates of economic growth. On the other hand, the new government began a rapprochement with the Middle East through the doctrine of "Zero Problems with Neighbors" - a region that for years was little explored by the traditional Turkish elites. However, with the start of the Arab uprisings and the outbreak of the conflict in Syria in 2011, Turkey again underwent an inflection in its foreign policy. The Turkish government adopted an assertive stance, assuming a position of great influence among both the Syrian conflict and the new Islamic political movements in the region. Given this context, this dissertation has as its research question the following: why Turkey changed its foreign policy in 2011, how has it been oriented since then and what aims has it sought. We will try to argue that this inflection in 2011 occurred due to two external shocks: the Arab revolts and a new US stance towards the Middle East; nonetheless, such new stance was only possible due to AKP’s domestic reforms. In addition, we will point out that in 2011 the Turkish government adopted a more assertive foreign policy, which aimed to place the country as a new regional leader through an emphasis on its political model. Finally, we will demonstrate that, over time, due to the radicalization of the Syrian war, Turkey again changed its foreign policy in 2015, also due to new external shocks, namely the achievement of Kurdish autonomy in Syria and the rise of the Islamic State. Since then, in a scenario of greater external constraints, the Turkish government would start to pay more attention to security issues, prioritizing problems arising from Syria, especially those related to the Kurdish issue